Role of Contract Farming in Increasing Agricultural Sustainability in India: A Quantitative Investigation - BHARDWAJ, RAJNEESH (International Journal of Psychosocial Rehabilitation, 2024)
A rise in the popularity of processed goods, changes in consumer behaviour, and supportive regulatory environments, farm centred on a partnership among peasants as well as agroprocessing and/or marketing corporations is becoming more popular in Indian farming. The rationale for the development of such a type of farming is to boost individual financing of the industry while lowering pricing hazards and post-harvest damages, particularly for commodities like largely priced fruit, greens, and high-risk vegetables. Small holdings might receive a wide range of assistance from the private industry, including input supply, product assembling, and sales. Considering this, the current research looks into the degree to which contract farming will free local farmers in Indian agriculture from their current burdens and aid their escape from the cycle of scarcity. It was noted that although contract farming does have the ability to tackle issues with access to markets (both input and output), modern tech, and economic stability, it additionally has the possibility of worsening issues with traditional knowledge deterioration, soil conditions, and prejudice against big farms. Stronger organizational structure is deemed necessary to increase the sustainability and inclusivity of farming activities. The sample size of the study was 183 respondents. The data analysis was performed with the help of t-test and mean.